Embolectomy at the Time of Ligation of Femoral Vessels in Psuedoaneurysm in Intravenous Drug Addicts can save Limb - Syed Hamad Rasool, Hafiz Khalid Pervaiz Butt, Mariam Arif, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the impact of embolectomy at the time of ligation of femoral artery in management of pseudoaneurysmin intravenous drug addicts Study design: Descriptive cross-sectional study Methods: This study was carried out at Vascular surgery department, CMH Lahore and included 28 patientsof intravenous drug addiction of both genders presenting in emergency of CMH Lahore with viable limb from 1st August 2021 to31st January 2023. Unsalvageable limbs at the time of presentation were excluded from the study. SPSS Version 20.0 was used for data analysis of age, sex, co-morbidities (infection), mode of presentation and outcome variables. Results: This study comprised of28 patientsadmitted through Emergency Department of CMH, Lahore. The mean age was found to be 32.16 years ±7.63 years. All patients 28(100%) were males with majority belonging to third decade of life 20(71.4%).Chronic viral infection was present in all cases. Almost half of them had hepatitis B virus infection (48%) while cases positive with hepatitis C virus and HIV infections were 37% and 15% respectively.Majority of the patients came to the hospital with bleeding from ruptured pseudoaneurysm (60.7%) and infected pulsatile swelling (32.1%), while pulsatile swelling without bleedingand wrong diagnosis were least common.Alllimbs were salvaged in first and second follow-up visits, 20 patients were lost on follow up on 12th week. Conclusion/Practical implication: Embolectomy is a very useful adjunct in the management of pseudoaneurysm of intravenous drug addicts. It should be routinely practiced in treatment of these patients to save limbs. Keywords: Embolectomy, ligation, femoral vessels, intravenous drug addicts